2020
DOI: 10.1111/ssqu.12857
|View full text |Cite
|
Sign up to set email alerts
|

Anxious About Social Violence: The Emotional Underpinnings of Support for Gun Control

Abstract: ObjectiveWe theorize that anxiety (fear) related to mass shootings and social violence increases support for gun control among the American public.MethodsWe support our theory with a regression discontinuity analysis based on an actual mass shooting, observational analyses from the same data set testing the relationship between fear and support for gun control, and two survey experiments that prime anxiety in the context of mass shootings and social violence.FindingsWe show that support for gun control increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A review of the public opinion on gun control literature yields at least three conclusions. First, in nearly every study on the issue, gun ownership is a predictor of gun control attitudes; specifically, gun owners are more likely than non‐owners to oppose gun control (Burton et al, 2020; Filindra, Collingwood, and Kaplan, 2020; Filindra and Kaplan, 2016, 2017; Kleck, Gertz, and Bratton, 2009; Wozniak, 2017). The logic underlying this finding is that those with reasons for owning a gun (e.g., for self‐defense and hunting) and self‐interest in maintaining their ownership status will oppose policies that threaten their ability to do so.…”
mentioning
confidence: 99%
“…A review of the public opinion on gun control literature yields at least three conclusions. First, in nearly every study on the issue, gun ownership is a predictor of gun control attitudes; specifically, gun owners are more likely than non‐owners to oppose gun control (Burton et al, 2020; Filindra, Collingwood, and Kaplan, 2020; Filindra and Kaplan, 2016, 2017; Kleck, Gertz, and Bratton, 2009; Wozniak, 2017). The logic underlying this finding is that those with reasons for owning a gun (e.g., for self‐defense and hunting) and self‐interest in maintaining their ownership status will oppose policies that threaten their ability to do so.…”
mentioning
confidence: 99%
“…Mark R. Joslyn and Donald P. Haider-Markel (2017) demonstrate that individuals who feel more anxious about mass shootings are more likely to support gun regulation measures. Alexandra Filindra, Loren Collingwood, and Noah J. Kaplan (2020) experimentally show that anxiety related to mass shootings and mass violence increases support for gun regulation. In addition, Mark R. Joslyn and Donald P. Haider-Markel (2017) found that respondents who were anxious about the 2016 Orlando nightclub shooting were more likely to support gun regulations.…”
Section: Threat and Attitudes Toward Gunsmentioning
confidence: 93%
“…Gun ownership is also consistently predictive of gun attitudes and a greater likelihood of adopting elements of US gun culture, which has been perpetuated by the NRA (Lacombe et al 2019). Other work finds that contextual effects also matter in determining individual-level gun attitudes, including living in an area that experienced a mass shooting (Barney & Schaffner 2019, Newman & Hartman 2019, which likely work via increased anxiety among local residents (Filindra et al 2020). Some work suggests that contextual and individual-level factors interact to impact gun attitudes; for instance, local levels of gun crime relate to gun policy among political Independents in the mass public, but not among Republicans or Democrats (Pearson-Merkowitz & Dyck 2017).…”
Section: Americans' Gun Policy Preferences and Rural Identitymentioning
confidence: 99%